2014
DOI: 10.1093/sysbio/syu090
|View full text |Cite
|
Sign up to set email alerts
|

Historical Species Distribution Models Predict Species Limits in WesternPlethodonSalamanders

Abstract: Allopatry is commonly used to predict boundaries in species delimitation investigations under the assumption that currently allopatric distributions are indicative of reproductive isolation; however, species ranges are known to change over time. Incorporating a temporal perspective of geographic distributions should improve species delimitation; to explore this, we investigate three species of western Plethodon salamanders that have shifted their ranges since the end of the Pleistocene. We generate species dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 81 publications
1
31
0
Order By: Relevance
“…All populations were allowed to expand (c = 0-5) and theta (h = 4N e l) was set between 0.01 and 5. Priors were based on previous Plethodon studies (Pelletier & Carstens, 2014;Pelletier et al, 2015) and past climatic fluctuations (Webb & Bartlein, 1992). A total of 6,000,000 simulations were conducted using ms (Hudson, 2002), and the following five summary statistics were calculated: {p, ss, D, h H , H}.…”
Section: Genetic Datamentioning
confidence: 99%
See 2 more Smart Citations
“…All populations were allowed to expand (c = 0-5) and theta (h = 4N e l) was set between 0.01 and 5. Priors were based on previous Plethodon studies (Pelletier & Carstens, 2014;Pelletier et al, 2015) and past climatic fluctuations (Webb & Bartlein, 1992). A total of 6,000,000 simulations were conducted using ms (Hudson, 2002), and the following five summary statistics were calculated: {p, ss, D, h H , H}.…”
Section: Genetic Datamentioning
confidence: 99%
“…The models were evaluated using area under the curve (AUC) and true skill statistic (TSS) scores. We also projected models for P. vandykei and P. larselli with data from Pelletier et al (2015) onto the Mid-Holocene bioclimatic data and compared the niches of P. dunni to the current and LGM models of these two species from Pelletier et al (2015).…”
Section: Species Distributional Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later ecological studies in the same geographic region found that the contact zones between parapatrically separated lineages of an endemic Californian salamander and potential incipient species were inhospitable for migrants and thus barriers to gene flow (66). These kinds of phylogeographic and landscape genetics studies, which integrate geographic and ecological analyses, have spawned new methods in species delimitation that explicitly consider the extent of ecological divergence when diagnosing species (66,(107)(108)(109). Thus, understanding the role of ecological and evolutionary processes across a landscape can be illuminating to the study of both the processes and the resulting biogeographic patterns of speciation.…”
Section: Ecological and Evolutionary Questions That Would Benefit Fromentioning
confidence: 99%
“…Dramatic changes in climate, hydrology and topography have long been 46 recognised to have lasting impacts on the diversity, distribution and divergence of 47 species and populations (Pelletier et al 2015). Understanding the relationship 48 between the historical environment and the genealogy of species remains critical for 49…”
Section: Introduction 45mentioning
confidence: 99%